Analysis of Policies and Regulations on Fire Prevention and Environmental Pollution in the Maritime Sector: A Case Study of the Azalia Tanker - Novan Muji Nugroho; K.P. Suharyono S. Hadiningrat; Febri Pramudya Wardani (Jurnal Cakrawala Akademika, 2025)
This study examines the effectiveness of policies and regulations in preventing fires and environmental pollution in the maritime sector, with a focus on the Azalia tanker ship as a case study. Using a qualitative case study approach, the research analyzes international conventions such as MARPOL and SOLAS, as well as national regulations, to assess their implementation on the Azalia tanker. Data were collected through document analysis and semi-structured interviews with crew members, regulators, and other stakeholders. The findings reveal that while the Azalia tanker is equipped with necessary safety and pollution prevention equipment, gaps in compliance persist due to aging infrastructure, limited resources, and insufficient crew training. The study highlights the importance of enhanced monitoring, simplified reporting systems, and regular training programs to improve policy implementation. Additionally, the integration of modern technologies such as AI and IoT is recommended to enhance fire detection and pollution monitoring. The research concludes that collaborative efforts among stakeholders, including shipping companies, regulators, and educational institutions